2020
DOI: 10.1016/j.heliyon.2020.e03327
|View full text |Cite
|
Sign up to set email alerts
|

Geo-investigation on groundwater control in some parts of Ogun state using data from Shuttle Radar Topography Mission and vertical electrical soundings

Abstract: Groundwater is a vital natural resource that plays a significant function in sustainability of living things on earth. Its exploration requires special skill for optimum exploitation. Shuttle Radar Topography Mission (SRTM)and Vertical Electrical Sounding (VES) were used to detectthe stratigraphy and subsurface structures controlling the groundwater system around Iju -Ota, Ogun State, Southwestern Nigeria. Nineteen (19) VES points were carried out where there were dense concentrations of lineaments and interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The results of this study are in agreement with the works of [93] and [94] who reported that the maximum depth to the aquiferous units within Atan-Ota axis, a brittle deformation zone, varied from 80 to 130 m.…”
Section: Basement Mapping and Structural Frameworksupporting
confidence: 93%
“…The results of this study are in agreement with the works of [93] and [94] who reported that the maximum depth to the aquiferous units within Atan-Ota axis, a brittle deformation zone, varied from 80 to 130 m.…”
Section: Basement Mapping and Structural Frameworksupporting
confidence: 93%
“…The prevailing sedimentary formation in the study area is the Benin Formation which is considered permeable as it consists of an alternation of sands and clay. Generally, the occurrence, accumulation, and movement of groundwater in the study area are primarily controlled by geology (Joel et al, 2020).…”
Section: Geology and Hydrogeology Of The Areamentioning
confidence: 99%
“…Steiner try to applied resistivity methods combined with seismic methods to investigate pollutants in groundwater (Steiner et al, 2022). Besides that, the resistivity method can also be used to identify groundwater potential (Joel et al, 2020), especially in areas that are still hard to get clean water supply or areas that require agricultural irrigation (Alarifi et al, 2022;Chikabvumbwa et al, 2021;Zaher et al, 2021). The difference in resistivity values due to the presence of salt minerals such as sodium chloride in the aquifer can also be used to analyze the phenomenon of seawater intrusion using this method (Ammar et al, 2021;Wilopo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%